2009
DOI: 10.1002/glia.20872
|View full text |Cite
|
Sign up to set email alerts
|

Altered functional properties of satellite glial cells in compressed spinal ganglia

Abstract: The cell bodies of sensory neurons in the dorsal root ganglion (DRG) are enveloped by satellite glial cells (SGCs). In an animal model of intervertebral foraminal stenosis and low-back pain, a chronic compression of the DRG (CCD) increases the excitability of neuronal cell bodies in the compressed ganglion. The morphological and electrophysiological properties of SGCs were investigated in both CCD and uninjured, control lumbar DRGs. SGCs responded within 12 hours of the onset of CCD as indicated by an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
96
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 105 publications
(112 citation statements)
references
References 48 publications
(51 reference statements)
9
96
0
3
Order By: Relevance
“…Kir4.1 is confined to SGCs of sensory ganglia, where it is proposed to control K ϩ concentrations in the perineuronal environment and thereby regulate neuronal excitability (13)(14)(15)(16)(17). In intact DRG, we found that Kir4.1-immunoreactive (IR) SGCs completely ensheathed NeuN-IR neurons ( Fig.…”
Section: Maintaining Neuron-sgc Interactions In Dissociated Andmentioning
confidence: 71%
See 1 more Smart Citation
“…Kir4.1 is confined to SGCs of sensory ganglia, where it is proposed to control K ϩ concentrations in the perineuronal environment and thereby regulate neuronal excitability (13)(14)(15)(16)(17). In intact DRG, we found that Kir4.1-immunoreactive (IR) SGCs completely ensheathed NeuN-IR neurons ( Fig.…”
Section: Maintaining Neuron-sgc Interactions In Dissociated Andmentioning
confidence: 71%
“…SGCs also express Kir4.1 and display a high K ϩ conductance that is hypothesized to control [K ϩ ] of the perineuronal environment and regulate neuronal excitability. Reduction in Kir4.1 expression and mediated currents has been demonstrated during inflammation, and Kir4.1 silencing in sensory peripheral ganglia enhances pain (13)(14)(15)(16)(17). In inflammatory pain and disease states, SGCs can release ATP and cytokines that may increase neuronal excitability (18 -21).…”
Section: Transient Receptor Potential (Trp)mentioning
confidence: 99%
“…Several studies correlate glial activation with an increase in the expression of different proteins, including GFAP (23,24). A neutralizing antibody against the FKN receptor (AbCX3CR1; 10 μg per DRG) was administered into the DRG (L5).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, blocking the activity of certain inflammatory cytokines in DRG partially relieves the CCD-induced hyperalgesia [16,17] . In addition, increased activity of satellite glial cells in the DRG has been recently shown to play an important role in CCD-induced neuronal hypersensitivity [18] . However, the mechanisms underlying the spread of mechanical and thermal hyperalgesia as well as mechanical allodynia observed in CCD mice remain still unclear and require further investigation.…”
Section: Discussionmentioning
confidence: 99%